POTENTIAL TOURISM OF KAMBAS NATIONAL PARKIN SUKADANA, LAMPUNG TIMUR REGENCYTOWARDS REGIONAL INDEPENDENCE - Dwi Ismaryati (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Indonesia is an archipelagic country that has natural resources that consist of oceans, sun, beaches and countries that allow it to be used as a source of foreign exchange. For regions that are blessed with exotic natural resources are expected to be able to contribute in providing foreign exchange for the region in order to achieve regional independence. The problems that occur how to market natural resources that consist of oceans, sun, beaches and abundant countries are assets that can provide a vision for local development. One effort that can be done is to make it a place. Market-driven sectors and industries. To market the items needed for all parties involved in management, government and society. This study aims to describe the tourism potential of the Way Kambas National Park in Sukadana, East Lampung Regency. The method used is descriptive method. The subject of the management research was set by 10 respondents. Techniques for exporting data, documentation and interviews. Data analysis uses a percentage table. The results showed that the Way Kambas National Park Tourism Object has a natural panoramic potential and socio-cultural potential. The total potential is 10 of the potential that there are 6 potentials that have been optimally developed and 4 potentials that have not been optimally optimized.Keywords: Potential, Tourism, Resources, Regional Independence